Disproportion and dysmorphism in an adult Belgian population with Turner syndrome: risk factors for chronic diseases?. Issue 4 (3rd July 2020) - Van De Kelft, An-Sofie; Lievens, Charlotte; De Groote, Katya; Demulier, Laurent; De Backer, Julie; T'Sjoen, Guy; Craen, Margarita; Callewaert, Bert; De Schepper, Jean
ABSTRACT: Background: Turner syndrome (TS) is characterized by dysmorphism and body disproportion. TS women are also susceptible to a range of chronic disorders including arterial hypertension (AHT), osteoporosis, sensorineural hearing loss (SNHL), type 2 diabetes mellitus (DM2) and thyroid disease. The association between dysmorphism/body disproportion and chronic disease has never been studied in TS women. The effect of growth hormone treatment on body disproportion is also unclear. Objectives: to analyze dysmorphic features and body disproportion in TS women in relation to the presence of chronic disease and to document the effect of growth hormone therapy on body disproportion. Method: 76 adult TS women with a regular follow up at the TS clinic UZ Ghent were invited to participate. Detailed body measurements were performed in 44 volunteering TS women. Scoring systems for overall dysmorphism, craniofacial dysmorphism, thoracic and limb abnormalities and skeletal disproportion were developed. Results: TS women with a higher dysmorphism score were more at risk for AHT (p = 0.04) as well as those with a higher sitting height/standing height ratio (p < 0.05). Prevalence of AHT, osteoporosis and DM 2 was lower in TS women treated with GH during childhood (p < 0.05). Conclusions: Adult TS women with relatively short legs or with more physical dysmorphic stigmata were more at risk for AHT. GH therapy does not seem to increase the risk of chronic disease on the long term.